2018
DOI: 10.1021/acschemneuro.8b00039
|View full text |Cite
|
Sign up to set email alerts
|

Genistein: A Dual Inhibitor of Both Amyloid β and Human Islet Amylin Peptides

Abstract: Abnormal misfolding and aggregation of amyloid peptides into amyloid fibrils are common and critical pathological events in many neurodegenerative diseases. Most inhibitors or drugs have been developed to prevent amyloid aggregation of a specific peptide, showing sequence-dependent inhibition mechanisms. It is more challenging to develop or discover inhibitors capable of preventing the aggregation of two or more different amyloid peptides. Genistein, a major phytoestrogen in soybean, has been widely used as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 54 publications
4
90
0
Order By: Relevance
“…However, it realizes moderate binding free energies (Gbind ~ -10 kcal/mol) in all sites, with the most stable complexes (Gbind ~ -20 kcal/mol) involving the β-2, and β-1 sites. These results are in agreement with the finding of a computational study recently reported by Ren et al [20] for a structurally homologous compound, genistein. They showed that genistein prefers to bind the β-sheet grooves to interfere with their self-aggregation.…”
Section: Putative Binding Sites and Binding Free Energiessupporting
confidence: 93%
See 1 more Smart Citation
“…However, it realizes moderate binding free energies (Gbind ~ -10 kcal/mol) in all sites, with the most stable complexes (Gbind ~ -20 kcal/mol) involving the β-2, and β-1 sites. These results are in agreement with the finding of a computational study recently reported by Ren et al [20] for a structurally homologous compound, genistein. They showed that genistein prefers to bind the β-sheet grooves to interfere with their self-aggregation.…”
Section: Putative Binding Sites and Binding Free Energiessupporting
confidence: 93%
“…Atomistic computer simulations are well suited to provide molecular-level details of amyloid oligomer and fibril interactions with ligands, helping in the future development and characterization of druggable modalities [12]. Basically four aspects of the flavonoids-amyloid interaction have been studied by computational methods: 1) the effect of ligands on the conformational transitions of Aβ monomers from initial random coil or α-helix into β-sheet structures [13,14] and ligand-mediated conformational change on Aβ dimer [15] by means of Replica Exchange Molecular Dynamics (REMD) simulations; 2) the effect of ligands on the aggregation of Aβ (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) using Coarse-Grained 2 of 15 Simulations [16]; 3) effect of ligands on the conformation and stability of amyloid-beta mutants [17] by Molecular Dynamics (MD) simulations; 4) preferential binding sites of ligands and their effect on amyloid structure-dynamics [18] on Aβ fragments and full-length single Aβ protofilament [19][20][21][22][23][24][25] by means of Docking experiments, MD simulations and Free Energy calculations.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported an inhibitor of Aβ aggregation by HW-155 from combinatorial screening. The possibility of cross inhibitory activity of amyloid inhibitors [32][33][34][35] toward multiple classes of protein fibrils prompted our effort to investigate its inhibition of hIAPP aggregation. To probe the importance of side chains on the aggregation of hIAPP, we synthesized a few derivatives of HW-155.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an urgent need for potent inhibitors of the process producing these pathogenic fibrils. In line with this, some inhibitors, including the peptides derived from the various secondary recognition elements along the amylin peptide chain [15][16][17] , engineered peptides [18][19][20] , constrained peptides [21][22][23][24][25][26][27] , small molecules 28,29 and natural products [30][31][32] , have been reported. Many of these inhibitors are specific in their activity; however, a good number of them have exhibited dual inhibitory activity such that they can inhibit amyloid aggregation of multiple classes of proteins non-specifically [32][33][34][35] .…”
mentioning
confidence: 94%
See 1 more Smart Citation